PENGARUH PENGETAHUAN INVESTASI, MODAL MINIMAL, DAN MOTIVASI INVESTASI TERHADAP MINAT MAHASISWA BERINVESTASI DI PASAR MODAL SYARIAH - Nurul Khofifah (JURNAL EKOBIS DEWANTARA, 2023)
This research was conducted with the aimed of knowing the effect of investment knowledge, minimum capital, and investment motivation on the interest of Islamic Financial Management students class of 2019-2021 at UIN Sayyid Ali Rahmatullah Tulungagung to invest in the Islamic capital market. The research approach with probability sampling. The result of the data were obtained by distributing a questionnarire with a slovin calculation of 90 respondets. Data analysis technique using multiple regression analysis. With the result of the test on the effect of investmen knowledge has a positive and significant effect on investment interest. Minimum capital has a positive and significant effect on investment interest. And investment motivation has a positive and significant effect on investment interest in the Islamic capital market.